A medical implant
Patent Information
- Application Number
- CN202521439869.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2035-07-10
AI Technical Summary
若为满足这些局部的高强度要求而提升整个植入物的纤维含量,则会使其整体刚度过高,重新引发严重的应力遮挡问题
本实用新型的混合纤维织物中,经线沿其排列方向的面密度呈非均匀分布,使得织物两边缘区域的经线密度高于其中心区域的经线密度,将其进一步堆叠,能够形成生物玻璃纤维含量由内至外梯度分布的生物复合材料。其中,生物复合材料外层的生物玻璃纤维含量较高,赋予医用植入物优异的表面硬度和局部强度(弯曲强度可达150至800 MPa),以骨螺钉为例,可使其表面的螺牙具有极高的抗剪切能力,解决了传统聚合物螺钉易滑丝、易崩裂的问题。而生物复合材料内层的生物玻璃纤维含量较低,有效降低了植入物的整体刚度(弹性模量可控制在16-27 GPa),显著缓解了应力遮挡效应,突破了传统生物复合材料“高强度必然高刚度”的限制。因此,该生物复合材料能够在结构上实现性能的按需分配,即在需要高强度的部位(如外表面和螺牙)实现力学性能强化,而在其他部位则保持较低刚度,从而在提供可靠固定的同时创造一个有利于骨骼愈合和整合的生物力学环境。
Smart Images

Figure CN224911544U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the field of medical materials technology, and more specifically, to a medical implant. Background Technology
[0002] In orthopedic surgery, medical implants used for internal fixation are crucial for treatment success. Commonly used medical implants include metallic implants and biodegradable polymer implants, but both types have their own drawbacks.
[0003] While metallic implants (such as titanium alloys) offer high strength, their elastic modulus is far higher than that of human bone, easily leading to a "stress shielding" effect that hinders normal physiological bone remodeling. They also typically require a second surgery for removal. Biodegradable polymer implants (such as pure polylactic acid PLLA) can avoid a second surgery, but their mechanical strength is insufficient to meet load-bearing requirements, and their acidic degradation products may trigger adverse tissue reactions, resulting in poor biocompatibility.
[0004] In related technologies, fiber-reinforced composite biomaterials show promise for improving the mechanical properties of medical implants. This involves uniformly mixing fiber materials and polymers, then fabricating the implant through processes such as injection molding and lamination. However, the homogeneous internal material distribution of implants produced using this process fails to address the core contradictions in mechanical performance. For example, in implants like bone screws, the head must withstand significant torque during insertion, while the threaded portion requires sufficient shear strength and long-term pull-out resistance. Increasing the overall fiber content to meet these localized high-strength requirements would result in excessively high overall stiffness, triggering severe stress shielding issues. Conversely, reducing the fiber content to decrease overall stiffness compromises the strength and reliability of critical components such as the screw tip and threads. Utility Model Content
[0005] The present invention aims to improve the overall mechanical properties, degradation characteristics and biocompatibility of current medical implants.
[0006] As a first aspect, the present invention provides a fiber-reinforced biocomposite material, the biocomposite material comprising multiple layers of mixed fiber fabric stacked sequentially, wherein the warp of each layer of the mixed fiber fabric is bio-glass fiber filament, the weft of each layer of the mixed fiber fabric is biodegradable polymer fiber filament, and the warp density of each layer of the mixed fiber fabric gradually increases from the center to both sides along the warp arrangement direction.
[0007] Optionally, the mixed fiber fabric includes a central region distributed along the warp direction, a transition region located on both sides of the central region, and an edge region located outside the transition region, wherein the warp density of the central region, the transition region, and the edge region increases sequentially.
[0008] Optionally, in the mixed fiber fabric, the spacing between two adjacent warp threads in the edge region ranges from 0.12 mm to 0.2 mm, the spacing between two adjacent warp threads in the transition region ranges from 0.25 mm to 0.4 mm, and the spacing between two adjacent warp threads in the center region ranges from 0.45 mm to 0.8 mm.
[0009] Optionally, the multiple layers of the mixed fiber fabric are stacked and rotated in the same direction in sequence.
[0010] Optionally, the offset angle between two adjacent layers of the mixed fiber fabric is 10° to 45°.
[0011] Optionally, the bio-glass fiber filament comprises multiple bio-glass fiber filaments with a diameter of 10 to 40 μm.
[0012] Optionally, the biocomposite material includes an inner core layer and an outer shell layer distributed radially, wherein the bioglass fiber content of the outer shell layer is higher than that of the inner core layer.
[0013] As a second aspect, the present invention also provides a medical implant comprising the fiber-reinforced biocomposite material as described in the first aspect.
[0014] Optionally, the medical implant is a bone screw, which comprises multiple layers of mixed fiber fabric stacked sequentially, and the thread angle of the bone screw is consistent with the offset angle of two adjacent layers of mixed fiber fabric in the bone screw.
[0015] Optionally, the bone screw includes an inner core layer and a shell layer, and the ratio of the thread depth of the bone screw to the thickness of the shell layer is 1:(1.2 to 1.5).
[0016] Compared with related technologies, this utility model has at least the following beneficial effects: In this invention, the areal density of the warp yarns along their arrangement direction is non-uniformly distributed, resulting in a higher warp density at the edges than at the center. Further stacking of these fabrics creates a biocomposite material with a gradient distribution of bioglass fiber content from the inside out. The outer layer of the biocomposite material has a higher bioglass fiber content, endowing the medical implant with excellent surface hardness and local strength (flexural strength reaching 150 to 800 MPa). Taking bone screws as an example, it enables the threads on the surface to have extremely high shear resistance, solving the problems of stripping and breakage common in traditional polymer screws. The inner layer of the biocomposite material has a lower bioglass fiber content, effectively reducing the overall stiffness of the implant (elastic modulus can be controlled at 16-27 GPa), significantly alleviating stress shielding effects, and breaking through the traditional limitation of "high strength necessarily means high stiffness" in biocomposite materials. Therefore, this biocomposite material can achieve on-demand performance distribution in its structure, that is, strengthening mechanical properties in areas requiring high strength (such as the outer surface and threads), while maintaining lower stiffness in other areas, thereby providing reliable fixation while creating a biomechanical environment conducive to bone healing and integration.
[0017] Furthermore, in biocomposite materials, bio-glass fibers continuously release bioactive ions such as calcium, magnesium, and silicon during degradation, which can actively induce osteoblast attachment and proliferation, accelerate bone ingrowth, and promote the formation of a strong osteogenic interface, achieving ideal biointegration. Simultaneously, the alkaline components produced by the degradation of bio-glass fibers can neutralize the acidic products of polymer degradation, effectively stabilizing the pH value of the local microenvironment. This ensures that the pH fluctuation range of the microenvironment around the implant is less than or equal to 0.8, reducing the risk of inflammatory reactions. Thus, the medical implant comprehensively achieves an optimized balance of mechanical properties and local reinforcement, excellent fixation strength and long-term support, and superior biocompatibility and osteointegration capabilities. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the structure of the mixed fiber fabric in an exemplary embodiment of the present invention; Figure 2 This is a schematic diagram of the preparation process of the bone screw in an exemplary embodiment of the present invention; Figure 3 This is a schematic diagram of the structure of the mixed fiber fabric stacked in an exemplary embodiment of the present invention; Explanation of reference numerals in the attached figures: 1. Blended fiber fabric; 1a. Bio-glass fiber filaments; 1b. Biodegradable polymer fiber filaments; 1c. Central region; 1d. Transition region; 1e. Edge region; 2. Bio-composite material; 2a. Inner core layer; 2b. Outer shell layer; 3. Bone screw. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of this utility model more apparent and understandable, specific embodiments of this utility model are described in detail below. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used in the description of this application is for the purpose of describing specific embodiments only and is not intended to limit this application; The term "comprising" and its variations as used herein are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in this utility model are used to distinguish different objects, not to describe a specific order or hierarchy. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, unless otherwise stated, "a plurality of" means two or more.
[0020] In related technologies, whether it is a single metal implant, a polymer implant, or a composite material homogenized implant, it is difficult to truly achieve a balance between overall mechanical properties, degradation characteristics, and biocompatibility in medical implants.
[0021] To address the problems existing in related technologies, this utility model provides a fiber-reinforced biocomposite material, which includes a multilayer mixed fiber fabric 1. The multilayer mixed fiber fabric 1 is stacked sequentially. The warp of each layer of mixed fiber fabric 1 is bio-glass fiber filament 1a, and the weft of each layer of mixed fiber fabric 1 is biodegradable polymer fiber filament 1b. The warp density of each layer of mixed fiber fabric 1 gradually increases from the center to both sides along the warp arrangement direction.
[0022] Figure 1 This is a schematic diagram of the structure of the mixed fiber fabric 1 in an exemplary embodiment of the present invention. Figure 1As shown, the hybrid fiber fabric 1 in this embodiment of the invention is woven from bio-glass fiber filaments 1a and biodegradable polymer fiber filaments 1b as warp and weft, respectively. The areal density of the warp fibers along their arrangement direction is non-uniformly distributed, resulting in a higher warp density in the two edge regions 1e than in the central region 1c. Stacking the hybrid fiber fabric 1 forms a biocomposite material 2 with a gradient distribution of bio-glass fiber content from the inside to the outside. Based on this gradient distribution, the biocomposite material 2 has a higher bio-glass fiber content closer to the outer surface. See details... Figure 2 As shown, the biocomposite material 2 comprises an inner core layer 2a and an outer shell layer 2b distributed radially. The outer shell layer 2b has a higher content of bioglass fibers than the inner core layer 2a. The higher bioglass fiber content of the outer shell layer 2b endows the medical implant with excellent surface hardness and local strength (flexural strength can reach 150 to 800 MPa). Taking the bone screw 3 as an example, it can give the threads on its surface extremely high shear resistance, solving the problems of easy stripping and breakage of traditional polymer screws. The lower bioglass fiber content of the inner core layer 2a effectively reduces the overall stiffness of the implant (elastic modulus can be controlled at 16-27 GPa), significantly alleviating the stress shielding effect. This breaks through the limitation of "high strength necessarily means high stiffness" in traditional biocomposite materials 2. Therefore, this biocomposite material 2 can achieve on-demand performance distribution in its structure, that is, it can strengthen mechanical properties in parts that require high strength (such as the outer surface or threads), while maintaining lower stiffness in other parts, thereby creating a biomechanical environment conducive to bone healing and integration while providing reliable fixation.
[0023] Furthermore, the bio-glass fiber filaments 1a enriched in the outer shell layer 2b continuously release bioactive ions such as calcium, magnesium, and silicon during degradation. These ions actively induce osteoblast attachment and proliferation, accelerate bone ingrowth, and promote the formation of a robust osteogenic interface, achieving ideal biointegration. Simultaneously, the alkaline components generated during the degradation of the bio-glass fiber filaments 1a neutralize the acidic products of polymer degradation, effectively stabilizing the pH of the local microenvironment. This ensures that the pH fluctuation range of the microenvironment surrounding the implant is less than or equal to 0.8, reducing the risk of inflammatory reactions. This results in an optimized balance of mechanical properties and local reinforcement, superior fixation strength and long-term support, and excellent biocompatibility and osteointegration capabilities in the medical implant, comprehensively improving its mechanical properties, degradation characteristics, and biocompatibility.
[0024] Alternatively, continue to refer to Figure 1 As shown, the mixed fiber fabric 1 includes a central region 1c distributed along the warp direction, a transition region 1d located on both sides of the central region 1c, and an edge region 1e located outside the transition region 1d. The warp density of the central region 1c, the transition region 1d, and the edge region 1e increases sequentially.
[0025] This invention further forms a gradient distribution of warp density between the central region 1c, the transition region 1d, and the edge region 1e in the mixed fiber fabric 1, which is beneficial to achieve uniform change of warp density, thereby improving the stability of overall mechanical properties while realizing the zoning of mechanical properties.
[0026] In some optional embodiments, in the mixed fiber fabric 1, the warp density of the edge region 1e is 3.5 to 10 times that of the warp density of the central region 1c. Specifically, the spacing between two adjacent warp threads in the edge region 1e may range from 0.12 mm to 0.2 mm, the spacing between two adjacent warp threads in the transition region 1d may range from 0.25 mm to 0.4 mm, and the spacing between two adjacent warp threads in the central region 1c may range from 0.45 mm to 0.8 mm.
[0027] In some optional embodiments, the bio-glass fiber filament 1a accounts for 35% to 70% of the mass of the mixed fiber fabric 1, which is 100% of the total mass. The bio-glass fiber filament 1a comprises multiple bio-glass fiber filaments with a diameter of 10 to 40 μm and a linear density of 60 to 120 tex.
[0028] In this embodiment of the invention, by further precisely controlling the thickness of the bio-glass fiber filament 1a in the mixed fiber fabric 1, and optimizing the ratio and interface bonding of the bio-glass fiber and polymer, it is beneficial to achieve a precise match between the mechanical strength decay rate and the bone healing cycle.
[0029] In some alternative embodiments, refer to Figure 3 As shown, the multi-layered mixed fiber fabric 1 is stacked and rotated in the same direction, with the offset angle between adjacent layers of mixed fiber fabric 1 ranging from 10° to 45°.
[0030] In this embodiment of the invention, during the stacking process of the mixed fiber fabric 1, each fabric layer is controlled to shift clockwise or counterclockwise at a set angle, and the shift angle of each layer of mixed fiber fabric is the same. This allows a threaded shape to be formed on the outer surface of the biocomposite material 2, which is beneficial for further processing of medical implants such as bone screws 3. Specifically, referring to... Figure 3 As shown, Figure 3 In this embodiment, α represents the offset angle, specifically the angle formed by connecting the corner points of two adjacent fabric layers at the same location to the center of the fabric. By matching the offset angle of the mixed fiber fabric 1 with the thread angle of the bone screw 3, and combining this with a high-strength outer layer structure, the pull-out resistance of the medical implant is significantly improved. It should be noted that the number of stacked layers of the mixed fiber fabric 1 in this embodiment can be controlled according to the actual required length of the medical implant.
[0031] Furthermore, the biocomposite material in this embodiment of the invention can be prepared according to the following method: Step 1: Using bio-glass fiber filament 1a as the warp and biodegradable polymer fiber filament 1b as the weft, a mixed fiber fabric 1 is obtained. The warp density of the mixed fiber fabric gradually increases from the center to both sides along the warp arrangement direction.
[0032] Step 2: Stack the multi-layer mixed fiber fabric 1 to obtain the mixed fiber preform.
[0033] Step 3: Vacuum hot pressing and curing of the mixed fiber preform to obtain bio-composite material 2.
[0034] In some alternative embodiments, the material of the biodegradable polymer fiber filament 1b is selected from at least one of polylactic acid, polyglycolic acid, polylactide, poly-L-lactide, poly-DL-lactide, polycaprolactone, polyglycolic acid, polyethanol lactic acid, polyamide, polyurethane, polybutylene succinate, and polydioxanone.
[0035] In some optional embodiments, the material of the bio-glass fiber filament 1a may be selected from at least one of silicate-based systems, phosphate-based systems, and silicate-based systems. As an example, the composition of the bioactive glass fiber spinning may include: 30 to 50 parts SiO2, 15 to 30 parts CaO, 5 to 20 parts Na2HPO4, and 0 to 1 part MgO.
[0036] In preparing biodegradable polymer fiber filament 1b, one of the aforementioned materials can be dissolved in an organic solvent and then wet-spun. Specifically, the biodegradable polymer solution is placed in a spinning barrel, the screw speed is controlled, and the fibers are uniformly extruded through the spinneret in the spinning box. After the fiber extrusion is stable, it undergoes drawing, washing, winding, and drying. The organic solvent can be selected from any one of dioxane, hexafluoroisopropanol, dichloromethane, and chloroform, and the mass concentration of the biodegradable polymer in the organic solvent can be 15 to 25 wt%. The low-temperature wet spinning process adopted in this invention can effectively preserve the integrity of the polymer chain and avoid its degradation at high temperatures.
[0037] Bio-glass fiber filament 1a can be produced by melt drawing, which involves sequentially melting the raw materials at high temperature, filtering the melt, extruding through a spinneret, stretching, and cooling. Specifically, the melting temperature can be set to 1000 to 1500°C, and the holding time can be 2 to 3 hours.
[0038] Optionally, in step three above, the temperature for vacuum hot-pressing curing of the biocomposite material 2 can be between 180 and 220°C, and the pressure can be between 10 and 20 MPa. Vacuum hot-pressing curing helps to further improve the density of the biocomposite material 2, minimize interlayer voids, and enhance the overall mechanical properties and structural stability of the material.
[0039] Another embodiment of the present invention provides a medical implant, which includes the biocomposite material described above.
[0040] Specifically, medical implants can be obtained by further cutting and processing the biocomposite material 2 using a CNC machine tool, followed by polishing and sterilization. Exemplary medical implant products may include, for example... Figure 2 The bone screws shown are bone tissue repair products such as bone screw 3.
[0041] In some alternative embodiments, refer to Figure 2 As shown, when the medical implant is a bone screw 3, the bone screw 3 includes multiple layers of mixed fiber fabric 1 stacked sequentially, and the bone screw includes an inner core layer 2a and an outer shell layer 2b. The thread angle of the bone screw 3 is consistent with the offset angle of two adjacent layers of mixed fiber fabric 1 in the bone screw 3, and the ratio of the thread depth of the bone screw 3 to the thickness of the outer shell layer 2b is 1:(1.2 to 1.5).
[0042] By matching the offset angle of the hybrid fiber fabric 1 with the thread angle of the bone screw 3, the threads on the surface of the bone screw 3 are designed to have extremely high shear resistance, significantly improving the pull-out force of the bone screw 3. At the same time, controlling the ratio of thread depth to the outer shell layer 2b ensures a balance between the strength and stability of the threaded connection.
[0043] The present invention will be described in detail below through specific embodiments and comparative examples to better understand the present invention.
[0044] Example 1 Raw material description Bio-glass fiber filaments: Medical-grade bio-glass fiber strands with a linear density of 60 tex, formed by twisting multiple monofilaments. The surface is then impregnated with a silane coupling agent. The raw material composition (molar parts) is: 50 parts SiO2, 30 parts CaO, 19 parts Na2HPO4, and 1 part MgO.
[0045] Biodegradable polymer fiber filaments: made of polycaprolactone-lactide copolymer (PLCL) fiber strands with a linear density of 60 tex, a relative viscosity of 1.29, and a glass transition temperature of 45 to 60°C.
[0046] Raw material pretreatment: The two fiber raw materials were vacuum dried in a vacuum drying oven at 50℃ for 12 hours to reduce their moisture content to ≤800 ppm.
[0047] Specific preparation steps: Step (1): Preparation of blended fiber fabric Reference Figure 3As shown, a programmable loom is used, with bio-glass fiber filaments as warp and biodegradable polymer fiber filaments as weft, woven in a plain weave. Through loom program control, the warp threads are non-uniformly distributed across the total fabric width: in the edge region 12mm from each side edge, the warp spacing is controlled at 0.15mm; in the transition region adjacent to the edge, each 6mm wide, the warp spacing is controlled at 0.3mm; and in the central region of the fabric, 20mm wide, the warp spacing is controlled at 0.6mm. The weft threads are arranged at a uniform density. Through this design, the final mass percentage of bio-glass fiber filaments in the fabric is controlled to be approximately 50%.
[0048] Step (2): Multiple layers of alternating stacking Continue to refer to Figure 3 The mixed fiber fabric prepared in step (1) is rotated and stacked counterclockwise, with the offset angle between two adjacent mixed fiber fabrics being 10°, to obtain the mixed fiber preform.
[0049] Step (3): Vacuum hot pressing curing The mixed fiber preform was placed in a mold and vacuum hot-pressed at 200℃ and 15MPa for 30 minutes. After cooling and demolding, a bio-composite material with a thickness of 5mm was obtained.
[0050] Step (4): Precision machining of bone screws like Figure 3 As shown, the biocomposite material obtained in step (3) is machined into a bone screw blank with a diameter of 4.0 mm and a length of 30 mm using a CNC lathe. Then, the bone screw blank is machined using a precision lathe to form a thread with a pitch of 1 mm and a thread depth of 0.5 mm, thus obtaining a bone screw.
[0051] Example 2 The difference between this embodiment and Embodiment 1 is that, in step (2), when stacking the fabrics, the offset angle between two adjacent layers of mixed fiber fabric is 20°. All other raw materials, preparation and processing steps are the same as in Embodiment 1.
[0052] Example 3 The difference between this embodiment and Embodiment 1 is that, in step (2), when stacking the fabrics, the offset angle between two adjacent layers of mixed fiber fabric is 30°. All other raw materials, preparation and processing steps are the same as in Embodiment 1.
[0053] Example 4 The difference between this embodiment and Embodiment 1 is that, in step (2), when stacking the fabrics, the offset angle between two adjacent layers of mixed fiber fabric is 45°. All other raw materials, preparation and processing steps are the same as in Embodiment 1.
[0054] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (1), the warp threads (bioglass fiber filaments) are evenly distributed at a spacing of 0.25 mm along the warp thread arrangement direction, without forming a density gradient. The remaining steps are the same as in Example 1.
[0055] Comparative Example 2 This comparative example uses commercially available absorbable polylactic acid (PLLA) orthopedic screws manufactured by Chengdu Dicon Biomedical Materials Co., Ltd., with a diameter of 4.0 mm.
[0056] Comparative Example 3 The difference between this embodiment and Embodiment 1 is that, in step (2), when stacking the fabrics, the offset angle between two adjacent layers of mixed fiber fabric is 90°. All other raw materials, preparation and processing steps are the same as in Embodiment 1.
[0057] Performance testing methods: The bone screws prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance testing.
[0058] Mechanical performance testing: Each group of samples was tested according to the standards ASTM D790 (bending performance) and ASTM F543 (bone screw pull-out force) (n=5).
[0059] Degradation behavior and pH fluctuation determination: Samples were immersed in simulated body fluid (SBF) at 37°C and pH 7.4 in a constant-temperature shaker. The pH value of the immersion solution was measured periodically, and the maximum pH fluctuation range over 6 months was calculated.
[0060] By comparing the above embodiments with comparative examples, the influence of the functional gradient structure and different stacking angles of this utility model on the key performance indicators of bone screws can be systematically verified.
[0061] The performance test results are shown in Table 1: Table 1. Mechanical Performance Test Results Data
[0062] As shown in Table 1, the bone screws prepared in this embodiment of the present invention exhibit significant superiority in overall performance compared to the comparative product.
[0063] First, in terms of mechanical properties, compared to commercially available pure polymer absorbable screws (Comparative Example 2), the elastic modulus of the bone screws in all embodiments of this invention reached 17.2 to 18 GPa, an increase of approximately 4.5 times, which is closer to the mechanical properties of human cortical bone. Simultaneously, compared to homogenized bone screws with uniformly arranged bio-glass fiber filaments (Comparative Example 1) and pure polymer absorbable screws, the pull-out resistance of the embodiments of this invention is also increased by at least 50%, providing more stable and reliable fixation strength. This strongly demonstrates the significant advantages of the bone screws in the embodiments of this invention in optimizing the biomechanical environment.
[0064] Secondly, regarding biocompatibility, the bone screws in this embodiment maintained a stable pH fluctuation of 0.75 during a 6-month in vitro degradation period, significantly lower than the comparative product (pH fluctuation as high as 3). This demonstrates that the bio-glass fiber filaments in this material can effectively neutralize the acidic substances generated by polymer degradation, creating a more stable and friendly microenvironment for cell growth and tissue healing.
[0065] Furthermore, by comparing Examples 1-4, it can be found that the mechanical properties of the implant can be effectively controlled by adjusting the offset angle of the mixed fiber fabric. For example, at an offset angle of 20° (Example 2), the pull-out force of the bone screw reaches its peak (220N), while when the offset angle reaches 90° (Comparative Example 3), both the elastic modulus and pull-out force of the bone screw show a decreasing trend. This indicates that the manufacturing method of this invention has high design flexibility and can customize the production of implants with specific mechanical biases according to different clinical application needs.
[0066] In summary, this invention successfully prepared a biocomposite material through gradient fabric design and multi-layer angle offset stacking process. This biocomposite material achieves significant breakthroughs in three core indicators: mechanical properties, fixation strength, degradation performance, and biocompatibility. Its elastic modulus can reach over 17 GPa, its pull-out force can reach over 190 N, and its pH value fluctuation is less than 0.8 within 6 months. Applying it to medical implants can effectively solve many problems in fields such as weight-bearing orthopedics.
[0067] Although the present invention has been disclosed above, its protection scope is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the protection scope of the present invention.
Claims
1. A medical implant, characterized in that, The medical implant comprises multiple layers of mixed fiber fabric stacked sequentially. The warp of each layer of the mixed fiber fabric is made of bio-glass fiber filaments, and the weft of each layer of the mixed fiber fabric is made of biodegradable polymer fiber filaments. The warp density of each layer of the mixed fiber fabric gradually increases from the center to both sides along the warp arrangement direction.
2. The medical implant according to claim 1, characterized in that, The mixed fiber fabric includes a central region distributed along the warp direction, a transition region located on both sides of the central region, and an edge region located outside the transition region, wherein the warp density of the central region, the transition region, and the edge region increases sequentially.
3. The medical implant according to claim 2, characterized in that, In the mixed fiber fabric, the spacing between two adjacent warp threads in the edge region ranges from 0.12 mm to 0.2 mm, the spacing between two adjacent warp threads in the transition region ranges from 0.25 mm to 0.4 mm, and the spacing between two adjacent warp threads in the center region ranges from 0.45 mm to 0.8 mm.
4. The medical implant according to claim 1, characterized in that, The multiple layers of the mixed fiber fabric are stacked and rotated in the same direction in sequence.
5. The medical implant according to claim 4, characterized in that, The offset angle between two adjacent layers of the mixed fiber fabric is 10° to 45°.
6. The medical implant according to claim 1, characterized in that, The bio-glass fiber filaments comprise multiple bio-glass fiber filaments with a diameter of 10 to 40 μm.
7. The medical implant according to claim 1, characterized in that, The medical implant includes an inner core layer and an outer shell layer distributed radially, wherein the bioglass fiber content of the outer shell layer is higher than that of the inner core layer.
8. The medical implant according to claim 1, characterized in that, The medical implant is a bone screw, which comprises multiple layers of mixed fiber fabric stacked sequentially. The thread angle of the bone screw is consistent with the offset angle of two adjacent layers of mixed fiber fabric in the bone screw.
9. The medical implant according to claim 8, characterized in that, The bone screw includes an inner core layer and an outer shell layer distributed radially, and the ratio of the thread depth of the bone screw to the thickness of the outer shell layer is 1:(1.2 to 1.5).